Epidemiological Assessment of Neglected Diseases in Children: Lymphatic Filariasis and Soil-Transmitted Helminthiasis - Ana M. Aguiar-Santos; Zulma Medeiros; Cristine Bonfim; Abraham C. Rocha; Eduardo Brandão; Tereza Miranda; Paula Oliveira; Emanuel S.C. Sarinho (Brazilian Society of Pediatrics, 2013)
Objective: To report the prevalence of lymphatic filariasis and intestinal parasitic infec- tions in school-aged children living in a filariasis endemic area and discuss about the therapeutic regimen adopted in Brazil for the large-scale treatment of filariasis. Methods: A cross-sectional study including 508 students aged 5-18 years old, enrolled in public schools within the city of Olinda, Pernambuco. The presence of intestinal para- sites was analyzed using the Hoffman, Pons and Janer method on 3 stool samples. The diagnosis of filarial infection was performed using the rapid immunochromatographic technique (ICT) for the antigen, and the polycarbonate membrane filtration for the presence of microfilariae. Descriptive statistics of the data was performed using EpiInfo version 7. Results: The prevalence of filariasis was 13.8% by ICT and 1.2% by microfilaraemia, while intestinal parasites were detected in 64.2% of cases. Concurrent diagnosis of filariasis and intestinal parasites was 9.4%, while 31.5% of students were parasite-free. Among individuals with intestinal parasites, 55% had one parasite and 45% had more than one parasite. Geohelminths occurred in 72.5% of the parasited individuals. In the group with filarial infection the prevalence of soil-transmitted helminthiasis was 54.5%. Conclusions: The simultaneous diagnosis of filariasis and intestinal parasites as well as the high frequency of geohelminths justify the need to reevaluate the treatment strate- gy used in the Brazilian filariasis large-scale treatment program.